Divine Law and Animal Rights: Ethical and Legal Perspectives in the Old and New Testaments - Stephanie Giselle Nicolaides - Doctoral candidate; Alexander George Nicolaides (Pharos Journal of Theology)
This article delves into the parallel natures of both the divine law and animal rights within the religious contexts of the Old and New Testaments. Employing a comparative approach, the paper inspects the developing perspectives on the treatment of animals in biblical scriptures, shedding light on the ethical and legal dimensions embedded in religious teachings. The study investigates key subtopics such as sacrificial rituals and moral imperatives, providing a nuanced understanding of the historical development of attitudes towards animals. Additionally, the analysis of this article encompasses ethical considerations, legal implications, and societal attitudes towards animals, drawing connections between ancient laws and contemporary discourse. Moreover, this article will look at the contemporary needs of society and how religious discourse and juristic principles can be applied to ensure the safety and rights of animals.